PENGARUH AKTIVA PAJAK TANGGUHAN DAN BEBAN PAJAK KINI DALAM MENDETEKSI INCOME MAXIMIZATION - Widiariani, Ni Made Ayu; Sukartha, I Made (E-Jurnal Akuntansi; Vol 10 No 3 (2015), 2015)
This study aims to detect the possibility of income maximization when seasoned equity offerings using the modified Jones model with deferred tax assets and current tax expense as a detector. Data used in the study was obtained from the financial statements of companies that conduct seasoned equity offerings activities in the period 2004-2013. This study uses 35 companies listed in Indonesia Stock Exchange as samples that have met the criteria for purposive sampling. The test results data using multiple linear regression analysis showed that only current tax can use to detect income maximization when seasoned equity offerings.
Keywords: income maximization, deferred tax assets, current tax expense, seasoned equity offerings